The Science Trifecta: Role sharing, role exchange and regional placement for grand problems - Grant, Georgia; Taylor-Offord, Sam (New Zealand Science Review, 2024)
This is an opinion piece formed through discussion and in response to a need for society’s voice to be represented in science. This isn’t a new problem, and we join many others imagining alternatives for the science system (Fazey et al., 2020; Funtowicz and Ravetz, 2020; Kukutai et al., 2021; MBIE, 2021, 2022; Aung et al., 2022; Urai and Kelly, 2023). Our intention is that this work will encourage critical thought and examination of the science system as the reader has experienced it. Although we present three specific reforms, our primary goal is to widen the discourse and thinking on system reform. Ultimately, we want the reader to ask themselves: is the science system sufficiently representative, connected and adaptive to address the problems of the future, and to empower the contributions of all of its parts towards this end? Our audience is everyone, but our perspective is only as two early-career Pākehā working in the Aotearoa-New Zealand science system, at Te Pū Ao - GNS Science. (This work does not reflect the opinion of Te Pū Ao). We welcome all thoughts on the Science Trident (Georgia: georgia.grant.nz@gmail.com, Sam: staylorofford@gmail.com).